SINTESIS DAN KARAKTERISASI KARBOKSI METIL SELULOSA TONGKOL JAGUNG - , PUJI LESTARI; , Prof. Dr. Ir. Djagal Wiseso Marseno, M. Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There are about 5,8131 million tons corncobs as agricultural waste in 2012. With high cellulose content and abundant amounts, corncob can be a potential source of cellulose for synthesis into CMC. The purposes of this research were to obtain information cellulose alternative source from corncob for material of CMC